RANCANG BANGUN ROBOT ARM BERBASIS RASPBERRY PI MENGGUNAKAN PRINTER 3D - Nanang Ali Sutisna (Jurnal Teknik Mesin dan Mekatronika (Journal of Mechanical Engineering and Mechatronics), 2022)
In the current era of technological development, robots are one of the important elements used to make it easier for humans to complete their work. Various types of robots are used with various uses to help do human work, one of them is the robot arm. In this study, the Robot Arm was made as an educational media where the components are made with a 3D printer using Polylactic Acid (PLA). This robot arm was designed using the SolidWorks 2020 application, then with finite element analysis (FEA) it can be found which part is the concentration of the load and a simulation is carried out to determine whether the components of this robot are safe to withstand the given load. Next, a robot arm controller was made using a Raspberry Pi microprocessor and developed an android smartphone mobile device application to control the robot arm via a bluetooth connection. This robot arm is designed to have 6 degrees of freedom (DOF) and the actuators used are servo motors, namely MG996R and SG90. The development of the robot arm controller program was made using the Python programming language on the Raspberry Pi, which was then transferred to the MIT app Inventor application on the android smartphone to drive the arm robot. The lifting capacity of this robot arm is 5 grams with a maximum size of 30x30x30 mm. The results of system testing on the robot arm show the accuracy of movement at a slow speed producing an average percentage of X-axis error is 3.23%, and Y-axis is 3.58%. While at medium speed it produces an average percentage of X-axis error is 10, 05%, and the Y-axis 7.62%., and at high speed the percentage of the X-axis error is 11.44%, and the Y-axis is 6.58%.